Kenya tax model: Value added tax simulation analysis - Shibia, Adan; Omune, Lensa; Mbuthia, Juneweenex; Diao, Xinshen; Oguso, Alex; Omwenga, Walter; Kiptoo, Elvis; Ali, Jecinta; Laichena, Joshua (Kenya Institute for Public Policy Research and Analysis, 2024)
Taxation can be used as a policy tool to influence economic behaviour, promote equity and achieve developmental goals. However, taxation can result in undesired outcomes if not well designed and implemented. Distortionary tax may adversely affect consumption, private sector investment (Adam and Bevan, 2014) and household welfare (de la Feria and Swistak, 2024). Kenya faces a similar trade-off between generating sufficient tax revenue to finance government programmes such as the Bottom-Up Economic Transformation Agenda (BETA) and mitigating potential adverse effects on domestic production and household welfare. The Value Added Tax (VAT) contributes about 30 per cent of Kenya’s total tax revenue (National Treasury, 2024). The average share of VAT to GDP for Kenya was 4.6 per cent between 2013/14 and 2023/24, comparable to that of East African Community (EAC) countries and Sub-Saharan African at 4.5 per cent (World Bank, 2024; East Africa Revenue Authorities Technical Committee, 2024), but lower than the 6.7 per cent for South Africa and the 5.2 per cent for lower-middle-income economies. VAT is a broad-based consumption tax, with tax incidence largely falling on the final consumers, and therefore any VAT policy changes have potential economy-wide implications. This is compounded by the fact that VAT is a regressive tax, meaning that low-income households spend a higher proportion of their income on vatable products compared to high income earners. The VAT in Kenya is currently imposed at a standard rate of 16 per cent, with certain essential goods, particularly primary agricultural produces, and services as VAT exempt or zero-rated.